Konflik Batin Tokoh Karsana dalam Novel Tabon Karya Margareth Widhy Pratiwi - Puspitasari, Novi; Rohmadi, Mohammad; Kurwidaria, Favorita (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2023)
Conflict is a special attraction for readers of literary works. Moreover, the conflict experienced by the character. Therefore, an in-depth analysis is needed to find out the inner conflicts contained in a literary work. Novels are a type of literary work that tells the story of people's lives where the conditions for the conflicts of the characters. The purpose of this study is to describe the inner conflict of the character Karsana in the novel Tabon by Margareth Widhy Pratiwi. This research is in the form of a qualitative descriptive using a literary psychology approach. The data of this study are quotes and dialogues contained in the novel Tabon by Margareth Widhy Pratiwi. The sources of data of this study are documents. The sampling technique in this study used purposive sampling technique. The data collection techniques used are document analysis. The validity test techniques used are theoretical triangulation and source triangulation. Data analysis techniques use interactive analysis techniques. The research procedure includes three stages, namely the preparatory stage, the research implementation stage, and the presentation stage of the research results.  The result of this study is that Karsana figures experience id dominance so that the personality structure in Karsana's character is an unbalanced personality.